Advances in Hodgkin Lymphoma: Including the Patient’s Voice - Smith, Christine Moore; Friedman, Debra L. (Frontiers in Oncology, 2022)
Since the initial treatment with radiation therapy in the 1950s, the treatment of Hodgkin lymphoma has continued to evolve, balancing cure and toxicity. This approach has resulted in low rates of relapse and death and fewer short and late toxicities from the treatments used in pursuit of cure. To achieve this balance, the field has continued to progress into an exciting era where the advent of more targeted therapies such as brentuximab vedotin, immunotherapies such as PD-1 inhibitors, and chimeric antigen receptor T-cells (CAR-T) targeted at CD30 are changing the landscape. As in the past, cooperative group and international collaborations are key to continuing to drive the science forward. Increased focus on patient-reported outcomes can further contribute to the goal of improved outcomes by examining the impact on the individual patient in the acute phase of therapy and on long-term implications for survivors. The goals of this review are to summarize recent and current clinical trials including reduction or elimination of radiation, immunotherapies and biologically-targeted agents, and discuss the use of patient-reported outcomes to help discern directions for new therapeutic regimens and more individualized evaluation of the balance of cure and toxicity.